2022
DOI: 10.3390/ijerph192416710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Load Carriage on Postural Sway and Relative Ground Reaction Forces in Special Police Officers: A Cross-Sectional Study

Abstract: Although excessive load carriage results in biomechanical gait changes, little evidence has been provided regarding its impact on postural sway. Therefore, the main purpose of this study was to determine whether heavier loads have effects on changing foot stability and postural sway in special police officers. Thirty male special police officers (age = 40 ± 6 years, height = 180 ± 5 cm, weight = 89 ± 8 kg) were assessed in four conditions: (1) carrying no load, (2) carrying a 5 kg load, (3) carrying a 25 kg lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the first study aiming to investigate the effects of a '3.5 kg load' on spatiotemporal and kinetic foot parameters during quiet standing. Previous evidence has confirmed that heavier loads may impact several foot characteristics during a quiet stance, including increases in the mean postural sway during a double stance, the center of pressure path length, the average velocity and the lengths of the minor and major axes with a decrease in the angle between the Y and major axes [11,20,25]. Evidence suggests that load carriages produce greater foot changes and affect body sway during standing, which directly disrupts the body's center of mass, causing it to shift from a point of stability to the boundaries of the base of support.…”
Section: Discussionmentioning
confidence: 96%
“…To the best of the authors' knowledge, this is the first study aiming to investigate the effects of a '3.5 kg load' on spatiotemporal and kinetic foot parameters during quiet standing. Previous evidence has confirmed that heavier loads may impact several foot characteristics during a quiet stance, including increases in the mean postural sway during a double stance, the center of pressure path length, the average velocity and the lengths of the minor and major axes with a decrease in the angle between the Y and major axes [11,20,25]. Evidence suggests that load carriages produce greater foot changes and affect body sway during standing, which directly disrupts the body's center of mass, causing it to shift from a point of stability to the boundaries of the base of support.…”
Section: Discussionmentioning
confidence: 96%
“…We found that participants who stood on an unstable surface while carrying an external load had the worst shooting scores and a lower percentage of COG. Previous studies have shown the adverse effects of load on soldier and police officer postural sway [ 8 , 9 ] and shooting accuracy [ 13 ]. Gil-Cosano et al [ 13 ] documented a 30% decline in shooting score when soldiers wore a backpack (19.5 ± 2.4 kg, equivalent to 24.2 ± 3.4% of their body weight).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors within military and law enforcement settings, such as the carriage of additional equipment (e.g., protective vests and backpacks) and the negotiation of uneven terrain, can adversely affect the balance of police officers and soldiers [ 1 , 5 , 7 , 8 ]. Consequently, this can impact their shooting prowess and overall capacity to endure in combat scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation